Unsur Serapan Bahasa Daerah dan Bahasa Asing dalam Novel Lelaki Pembawa Kain Kafan - Elvina Syahrir (Balai Bahasa Provinsi Riau, 2019)
This research was motivated by the fact that literature as the imaginative works that in their use of language could get the loanwords of the local language or the foreign language. The author of the story was free to express through words. This research was a review of the novel Lelaki Pembawa Kain Kafan by Griven H. Putra, one of the writers in Riau Province. This study aimed to describe the elements of loanwords of the local language and the foreign language loandwords that were mentioned in the novel and grouping them based on the level of integration. Based on the analysis, it was obtained that novel loan the vocabularies of some languages namely Malay of Rantaubaru (Pelalawan, Riau), Javanese language, English, and Arabic. There were two groupings based on the level of integration in the novel. The results indicate that we were suggested to maintain and preserve the literary work.